Analysis of Essential Oil Compositionand Antimicrobial Effect of Stachys discolor subsp. mazandarana - Niyousha Souri; Mohammad Reza Monsef-Esfehani; Mahdi Vazirian; Nasrin Samadi; Seyede Nargess Sadati Lamardi (Tehran University of Medical Sciences, 2020)
Research on the antimicrobial effects of herbal extracts and natural compounds has proven that herbs have valuable sources of anti-infective agents, and numerous new compounds have been introduced to the market in this regard. The aim of the present study was to investigate the antimicrobial effectsof Stachys discolor subsp.mazandarana and to analyze the essential oil constituents of thisherb.Antimicrobial effects of ethanol (80%)extract and n-hexane, and chloroform fractions were investigated against three gram-positive bacteria (Staphlococusaureus, Streptococusmutans, andBacillus subtilis), one gram-negative bacterium (Escherichia coli), and also a fungus (Candidaalbicans) by well plate and agar dilution methods and diameter of the zone of inhibition was determined. The essential oil of the herb aerial parts was extracted by water distillation method and the essential oil compounds were analyzed by GC-Mass.The results of the present study showed that total extract of S. discolor subsp.mazandaranaand its various fractions had almost no antimicrobial activity and their minimum inhibitory concentration (MIC) was more than 100 mg / ml. Analysis of essential oils showed that anymol (alpha-bisabolol) (18.10%) andcurcumene (13.20%) were the most abundant components.The results revealed that the studied herb had no antibacterial and antifungal effects. However, given the compounds in the essential oil of this herb, it can be supposed that it may have significant analgesic and anti-inflammatory effects that can be investigated in future studies.